Analysis Influence Management Capital Work, Company Size and Capital Structure To Profitability - Lubis, Biman Paturahman; Riyadi, Rizal; Suharmiati, Suharmiati (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Globalization is an era in which the business world is required to become more effective in running its business. This is because there are no more boundaries that arise between countries. Included in business and business competition. Every company is required to be able to manage their company well in order to compete with other companies both for domestic companies and foreign companies. One indicators that can be used to assess well-managed companies is how these companies manage their working capital. This study aims to determine the Effect Analysis of Working Capital Management, Company Size, and Capital Structure on Profitability Cases Studies in Coal Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange. The population in this study is the Coal Sub Sector Mining Companies Listed on the Indonesia Stock Exchange. The samples used were six companies with five years of data, namely the 2017-2021 period. The method used in this study is multiple linear regression analysis which is an analysis that describes the shape of one or more variables with other variables. The type of data used is the type of secondary data. This study aims to determine the effect of Working Capital Turn Over, Firm Size and Capital Structure (debt to equity ratio) on Return on Assets partially and simultaneously. From the results of the regression analysis test, the results of the study partially shows that Working Capital Turn Over (X1) does not affect the Return on Assets of Mining Companies in the Coal Sub Sector, which means that H1 is rejected, size (X2) affects the Return on Assets of Mining Companies in the Rock Sub Sectors Bara, which means that H2 is accepted, and the debt to equity ratio (X3) has no effect on the Return on Assets of Mining Companies in the Coal Sub- Sectors, which means that H3 is rejected. Simultaneously it shows that Working Capital Turn Over (X1), size (X2) and debt to equity ratio (X3) affect the Return on Assets of Mining Companies in theCoal Sub Sectors, which means H4 is accepted. Keywords : Working Capital Management, Company Size, Capital Structure and Profitability